Conceptual Metaphor and Polysemy - Nigora Sobir qizi Jumaboyeva (Indonesian Journal of Innovation Studies, 2022)
This article deals with the conceptual metaphor and polysemy. Author tries to prove polysemy, which, along with conceptual metaphor, is one of the main mental processes, becomes a catalyst for the development of meaning and the generation of new meanings, and the possibility of its appearance is due to the anthropocentrism of communication itself and human experience. In addition, author provides several notions of prominent linguists who contributed in the sphere of metaphor and polysemy.